Dynamics of Viral and Host Immune Cell MicroRNA Expression during Acute Infectious Mononucleosis - Kaul, Vandana; Weinberg, Kenneth I.; Boyd, Scott D.; Bernstein, Daniel; Esquivel, Carlos O.; Martinez, Olivia M.; Krams, Sheri M. (Frontiers in Microbiology, 2018)
Epstein Barr virus (EBV) is the etiological agent of acute infectious mononucleosis (IM). Since acute IM is a self-resolving disease with most patients regaining health in one to three weeks there have been few studies examining molecular signatures in early acute stages of the disease. microRNAs have been shown, however, to influence immune cell function and consequently the generation of antibody responses in IM. In this study, we performed a comprehensive analysis of differentially expressed microRNAs in early stage uncomplicated acute IM. microRNAs were profiled from patient peripheral blood obtained at the time of IM diagnosis and at subsequent time points, and pathway analysis performed to identify important immune and cell signaling pathways. We identified 215 differentially regulated microRNAs at the most acute stage of infection when the patients initially sought medical help. The number of differentially expressed microRNAs decreased to 148 and 68 at one and two months post-primary infection, with no significantly changed microRNAs identified at seven months post-infection. Interferon signaling, T and B cell signaling and antigen presentation were the top pathways influenced by the microRNAs associated with IM. Thus, a dynamic and regulated expression profile of miRNA accompanies the early acute immune response, and resolution of infection, in IM.